Possible Atmosphere and Ionospheric Anomalies of the 2019 Pakistan Earthquake Using Statistical and Machine Learning Procedures on MODIS LST, GPS TEC, and GIM TEC - Amna Hafeez; Munawar Shah; Muhsan Ehsan; Punyawi Jamjareegulgarn; Junaid Ahmed; M. Arslan Tariq; Shahid Iqbal; Najam Abbas Naqvi (My University, 2021)
Identifying atmospheric and ionospheric anomalies based on remote sensing satellites has contributed highly to develop the hypothesis of lithosphere-atmosphere-ionosphere coupling (LAIC) over the Earthquake (EQ) epicenter during the seismic preparation period. This paper has investigated the variations of potential EQ precursor in daytime and nighttime Land Surface Temperature (LST) before and after the 2019 Pakistan EQ from MODIS (Moderate Resolution Imaging Spectroradiometer) satellite. The nighttime LST values of MODIS exhibit temporal anomalies during nighttime period within a time window of 5 days before and after the main shock day. Furthermore, the LST values predicted by Artificial Neural Network (ANN) validate the significant enhancement in nighttime time series of MODIS. The nighttime LST anomalies obtained from the observation and ANN prediction are more than 20% and 7% of normal distribution beyond the confidence bounds, respectively, within 5 days after the main shock. Likewise, the ionospheric anomaly from daily Total Electron Content (TEC) values at Sukkur Global Positioning System (GPS) station confirms the EQ associated ionospheric perturbations on the day after the main shock. The Global Ionospheric Maps (GIMs) also show the TEC anomalies during 1000-1400 LT on September 25, 2019.
Keywords: Anomaly (physics); Moderate-resolution imaging spectroradiometer; Epicenter; Earthquake Detection and Analysis